The Influence Of Digital Marketing And Price Discounts On Cokroaminoto University Yogyakarta Students' Purchasing Decisions On The Shopee Shopping Platform - Nugraha Dwi Permana; Rinaldi (Penerbit Hellow Pustaka, 2024)
This research aims to determine the influence of digital marketing and price discounts on Cokroaminoto University Yogyakarta students' purchasing decisions on the Shopee shopping platform. The data collection technique in this research used a purposive sampling technique with a total of 94 respondents who were students at Cokroaminoto University, Yogyakarta who used or had shopped on the Shopee shopping platform. The analytical test tools used in this research are the multiple linear regression test and the coefficient of determination test (R2). So the hypothesis tests used are partial significance tests (T test) and simultaneous significance tests (F test). The results of this research show that: 1) digital marketing has a significant influence on students' purchasing decisions, this is proven by the results of tcount > ttable or 6.058 > 1.661, and a significance value of 0.000 < 0.05. 2) price discounts have no influence on students' purchasing decisions, this is proven by the results of tcount < ttable or 1.649 < 1.661, and a significance value of 0.102 > 0.05. 3) digital marketing and price cuts simultaneously have a significant influence on students' purchasing decisions, this is proven by the results of fcount > ftable or 43.868 > 3.94, and a significance value of 0.000 < 0.05.